Evaluation of salivary calcium, phosphorus and alkaline phosphatase concentrations before and after the first phase of periodontal treatment in patients with chronic periodontitis - Jaber Yaghini; Samaneh Khashei; Zohreh Afshari; Ahmad Mogharehabed (Tabriz University of Medical Sciences, 2020)
Background. Evaluation of salivary biomarkers is a non-invasive, convenient, and economical method for diagnosing many diseases. Evidence shows that salivary biomarkers and periodontal disease might be correlated. This study was conducted to evaluate phase I periodontal therapy's effect on salivary concentrations of calcium, phosphorous, and alkaline phosphatase (ALP). Methods. In this descriptive, analytical study, 16 patients were selected from those referred to the Department of Oral Medicine, Faculty of Dentistry, Isfahan University of Medical Sciences, using convenience sampling. Salivary samples were collected using the drooling method. The salivary concentrations of calcium, phosphorous, and ALP were measured immediately after saliva collection, before the first phase of periodontal therapy and one month later, using a colorimetric assay. The data were analyzed with SPSS using paired t-test. P<0.05 was considered statistically significant. Results. The salivary concentrations of calcium, phosphorous, and ALP were 6.68, 20.57, and 48.31 mg/dL, respectively, before and 7.15, 22.51, and 40.37 mg/dL, respectively, after phase I periodontal therapy. There were no significant differences between the salivary levels of calcium, phosphorous, and ALP before and after phase I periodontal therapy (P>0.05). Conclusion. This study revealed that the salivary concentrations of calcium, phosphorous, and ALP remained relatively unchanged after phase I periodontal therapy.